2020
DOI: 10.14264/5d0bea7
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional CFD Simulation of Blood Flow in Aortic Dissection

Abstract: Aortic dissection is a serious cardiovascular condition where tears in the aortic wall lead to blood flow in between arterial tissue layers, separating the tissue and forming a false lumen. Knowledge of the blood flow dynamics for patients with aortic dissection can inform the treatment of aortic dissection. This paper aims to present haemodynamic metrics found in aortic dissection. In this study, individual patient-specific geometry and pulsatile flow velocity data is extracted from computed tomography (CT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…A plethora of methods for the simulation of blood pressure gradient of aortic coarctation models at rest and under exercise conditions were presented during the first and second Medical Image Computing and Computer-Assisted Intervention (MICCAI) CFD Challenge [28,29]. Wang et al [30] present haemodynamic metrics found in aortic dissection and quantitative indexes for optimal treatment planning. Moreover, Garje et al [31] observed numerical changes in vessels' blood flow and their growth due to an accumulation of cholesterol in coronary artery disease (CAD).…”
Section: Prior Aorta Simulation Methodsmentioning
confidence: 99%
“…A plethora of methods for the simulation of blood pressure gradient of aortic coarctation models at rest and under exercise conditions were presented during the first and second Medical Image Computing and Computer-Assisted Intervention (MICCAI) CFD Challenge [28,29]. Wang et al [30] present haemodynamic metrics found in aortic dissection and quantitative indexes for optimal treatment planning. Moreover, Garje et al [31] observed numerical changes in vessels' blood flow and their growth due to an accumulation of cholesterol in coronary artery disease (CAD).…”
Section: Prior Aorta Simulation Methodsmentioning
confidence: 99%
“…There were still many other strategies for improving numerical efficiency, for instance, new computational fluid dynamics (CFD) code (Hanka et al, 2014), hierarchical adaptive mesh refinement (HAMR) technique (Coirier and Bayyuk, 2002) and adaptive virtual cell embedding (VCE) method (Tang, 2007(Tang, , 2008. Wang et al (2017) proposed an overset grid meshing strategy based on a component view, which allows for idealized meshes in an automated fashion.…”
Section: Blast Wave Propagating In Complex Urban Areasmentioning
confidence: 99%